Plasma source ion implantation for ultrashallow junctions: Low energy and high dose rate - Cho, J; Han, S; Lee, Y; Kim, OK; Kim, GH; Kim, YW; Lim, H; Jung, HS (INST PURE APPLIED PHYSICS, 2001)
Ultrashallow p(+)/n junctions fabricated by plasma source ion implantation (PSII) were studied. After as-implanted samples were spike-annealed at 1000 degreesC and annealed for 5 sat 1000 degreesC, for samples with a background doping concentration of 6x10(17)#/cm(3), ultrashallow junction depths of 548 Angstrom and 745 Angstrom, respectively, could be obtained with an implant energy of 0.5 keV. Also, sheet resistances of 330 Omega/rectangle and 228 Omega/rectangle were acquired, respectively. These junction depths and sheet resistances obtained by the PSII process were found to satisfy 0.15 mum metal oxide semiconductor field effect transistor (MOSFET) applications.
Keywords: TRANSIENT ENHANCED DIFFUSION; SILICON; BORON